Rapid detection of paraquat residues in green tea using surface-enhanced Raman spectroscopy (SERS) coupled with gold nanostars. (December 2021) - Lin, Min-Hui; Sun, Lin; Kong, Fanbin; Lin, Mengshi
Abstract: As consumers demand safer food products, constant monitoring of pesticide residues in food is crucial. Conventional chromatography-based analytical methods are destructive and require time-consuming sample preparations. This study aims to establish a novel, facile, and rapid testing technique using surface-enhanced Raman spectroscopy (SERS) coupled with gold nanostars as a SERS substrate. The SERS performance was evaluated by detecting a widely used pesticide, paraquat, in green tea samples. Spiky tips of gold nanostars can serve as SERS hot spots to intensify Raman signals of analyte molecules. Additionally, the rough topography of gold nanostars has increased surface area, enabling good substrate-analyte interactions. Electron microscopes and Zetasizer were employed for the characterization of gold nanostar substrate. The detection limit of this SERS method is 0.2 mg/kg for paraquat in green tea. The results indicate that SERS coupled with gold nanostars is a practical approach and has great potential to be applied for qualification and quantification of trace contaminants in foods. Highlights: Novel gold nanostars were synthesized with multiple outwardly radiating branches. SERS coupled with gold nanostars was utilized to detect paraquat in green tea. PLS models were built for prediction of paraquat in green tea (R = 0.99). The detection limit of the SERS method for paraquat is 0.2 mg/kg. SERS method is a facile and rapid method for trace analyses of food contaminants.